Toxicity of engineered nanomaterials mediated by nano–bio–eco interactions. (2nd January 2018) - He, Xiaojia; Fu, Peter; Aker, Winfred G.; Hwang, Huey-Min
ABSTRACT: Engineered nanomaterials may adversely impact human health and environmental safety by nano–bio–eco interactions not fully understood. Their interaction with biotic and abiotic environments are varied and complicated, ranging from individual species to entire ecosystems. Their behavior, transport, fate, and toxicological profiles in these interactions, addressed in a pioneering study, are subsequently seldom reported. Biological, chemical, and physical dimension properties, the so-called multidimensional characterization, determine interactions. Intermediate species generated in the dynamic process of nanomaterial transformation increase the complexity of assessing nanotoxicity. We review recent progress in understanding these interactions, discuss the challenges of the study, and suggest future research directions.